Cellulose acetate polyethersulfone (CA-PS) blend ultrafiltration membranes of palm oil mill effluent treatment - Ani Idris, author; Iqbal Ahmad, 1974-, author; International Conference on Environment : Survival and Sustainability (2007: Turki) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL